Design optimization of a solar system integrated double-skin façade for a clustered housing unit - Barone, Giovanni; Vassiliades, Constantinos; Elia, Christina; Savvides, Andreas L.; Kalogirou, Soteris A. (My University, 2023)
The study compares a conventional double façade (DF), a building-integrated photovoltaic double façade (BIPV DF), and building-integrated photovoltaic thermal double façade (BIPVT DF), by considering the impact of the depth of the cavity between the photovoltaic system and the façade. The problematization aims at augmenting the function of an interstitial spaces between building envelope and programmed space both in terms of spatial expansion, but also in terms of energy production. The approach involves examining this space in terms of its spatial parameters and ability to accept an architecturally integrated solar system. To conduct the present analyses, three distinct systems were employed and applied to a sample thermal zone, where the cavity space shaped by the double façade was considered as a veranda space. The energy systems were modelled utilizing the commercial software DesignBuilder, and various dynamic simulations were performed using the building energy simulation software EnergyPlus for a representative South-Eastern Mediterranean weather zone. A parametric analysis was conducted, which involved varying the cavity depths from 0.25 m to 1.50 m. Results show that the conventional DF system demonstrates lower heating demands than the other systems, whereas the opposites occur for the cooling needs. Furthermore, an increase in the cavity depth between the PV system and the façade resulted in an increase in heating thermal loads and a decrease in cooling loads. The primary energy minimization approach provided interesting results, including the optimal depth cavity of the veranda (0.97 m).
Keywords: Building integrated photovoltaic-thermal; Building integration; Double façade; Energy analysis; Sustainable architecture